GUNCANGAN PENDAPATAN DAN PENGHALUSAN KONSUMSI RUMAH TANGGA DI PERDESAAN INDONESIA - Budiningsih, Ni Ketut Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
This study analyzes consumption smoothing due to income shocks in rural Indonesia. Income shocks are analyzed through shocks due to natural disaster, illness, job loses, and crop failure. This study uses panel data from Indonesian Family Life Survey (IFLS) 3 and IFLS 4. Analytical tool has used is regression to estimate income equation and consumption equation. This study uses Wald Test to analyze consumption smoothing. This study shows that nonagricultural asset and nonbusiness asset are kinds of assets that influence the income of rural household. Crop failure is kind of income shock that negatively affects income of rural household. Wald Test result shows that the rural households tend to do consumption smoothing when the income shocks exist.